2019
DOI: 10.1021/acs.jpclett.9b00439
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Nanocrystal Structural Disorder by Ligand Exchange: An Experimental and Theoretical Analysis

Abstract: Nanocrystals (NCs) present unique physicochemical properties arising from their size and the presence of ligands. Comprehending and controlling the ligand− crystal interactions as well as the ligand exchange process is one of the central themes in NC science nowadays. However, the relationship between NC structural disorder and the ligand exchange effect in the NC atomic structure is not yet sufficiently understood. Here we combine pair distribution function analysis from electron diffraction data, extended Xr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 29 publications
3
26
0
Order By: Relevance
“…The meta-like position 3 is unstable, favoring hydrogen migration to the ortho-like position 2. Fluorine induces a noticeable effect on binding energies, which are approximately two times stronger, and act in longer ranges (H at position 6 is almost 5 Å from the F atom), as also verified by the pair distribution function [62,63] of the hydrogen-fluorine pairs (Figures S1, S2). This indicates that F can act as an anchor, boosting hydrogen storage.…”
Section: Resultssupporting
confidence: 59%
“…The meta-like position 3 is unstable, favoring hydrogen migration to the ortho-like position 2. Fluorine induces a noticeable effect on binding energies, which are approximately two times stronger, and act in longer ranges (H at position 6 is almost 5 Å from the F atom), as also verified by the pair distribution function [62,63] of the hydrogen-fluorine pairs (Figures S1, S2). This indicates that F can act as an anchor, boosting hydrogen storage.…”
Section: Resultssupporting
confidence: 59%
“…1(b) we report the total and partial pair distribution function (PDF) of a-Bi 2 Se 3 . As expected for an amorphous phase, the PDF converges to unity for large distances, losing peak coherence, and indicating long-range disorder [87,88]. For small r, we observe two defined peaks for the first and second-neighbor pairs.…”
Section: A Amorphous Bi2se3supporting
confidence: 68%
“…the effect of ligands, solvent, or the atmosphere. 103,[105][106][107] For example, Zhang et al studied the dependence of the atomic structure on hydration in 3 nm ZnS particles. 108 The particles were synthesized in anhydrous methanol, and using PDF analysis, it was found that the assynthesized nanoparticles were highly disordered as reected by the less than 1 nm coherent scattering domain seen from the PDF.…”
Section: Nanostructure From Pdf Analysismentioning
confidence: 99%